Kesantunan Berbahasa Generasi Milenial pada Media Sosial di Era Digital - Nirwana Nirwana; Ratna Ratna (TEKSTUAL, 2022)
This research aims to understand the millennial generation's language politeness on social media in the digital era. It shows that politeness, courtesy, ethics are procedures, customs, or habits that apply in society. Unity is a rule of behavior that is determined and mutually agreed upon by certain communities which makes unity is at the same time a prerequisite that is mutually agreed by social behavior. The results of this resarch are: (1) The millennial generation needs to pay attention to the importance of politeness in language conveyed on social media. (2) The younger generation needs to consider and choose wisely on the the utterance or speech delivered on social media.